Profil Kemampuan Berpikir Kritis Siswa Field-Dependent dan Field-Independent dalam Menyelesaikan Persamaan Kuadrat - Liza, Tasya Dwi; Zahari, Cut Latifah; Panjaitan, Dedy Juliandri (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
The purpose of this study is to describe students' critical thinking skills in solving quadratic equation problems based on cognitive style. This research method uses a qualitative method using a cognitive style questionnaire and a critical thinking test. The subjects of this study were 6 students with field dependent cognitive styles and field independent cognitive styles. The results of the study stated that students who have a field dependent cognitive style cannot meet the critical thinking indicators because they cannot provide appropriate solutions. Students with a field independent cognitive style can meet all critical thinking indicators, namely interpretation, analysis, evaluation, and inference. Based on this study, it is necessary to train students' critical thinking skills by providing everyday problems by paying attention to the cognitive style possessed by students